“THE BRAÇOS ABERTOSPROGRAM” AND DRUGS POLITICS AT THE CONTROL SOCIETY”: a historical-anthropological dialogue. - BRANDÃO, BEATRIZ; CARVALHO, JONATAS (Outros Tempos: Pesquisa em Foco - História, 2018)
Abstract: The purpose of this article is to comprehend some of the directions taken in the context of drug policy within a control society, presenting and problematizing these two concepts. For that, a political program was analyzed that is distinct from the current definitions and practices found until now. The program to be analyzed is the “Programa de Braços Abertos (DBA)”, which was implemented under the management of Fernando Haddad, between 2014 and 2016, in the region of “Cracolândia”, in São Paulo.This region is recognized by the political interventions with the hygienist and compulsory practices that go against individual freedoms. In order to understand the new vision and action brought by the DBA against a historical repetition of managements and operations, there was a reflection on biopolitics, the work of pastoral programs and the place of DBA within the set of drug device technologies. At this point, another objective developed was to stablish the new ordinances of treatment models, such as Harm Reduction and Therapeutic Communities. Keywords: Drug Policy.Pastoral Programs.Harm Reduction.Therapeutic Communities.Cracolândia.De Braços Abertos.